Anaerobic treatment of effluent from SCR processing and water hyacinth - Huang; Fang Ri-Ming (Proceedings of IRRDB Symposium 1999, Hainan, Peoples Republic of China. pp.518-523.)
In this paper the preparation of methane from the anaerobic fermentation of the effluent from standard Chinese Rubber (SCR) processing and the water hyacinth planted in the anaerobic pond were studied. The results show that the water hyacinth is a good kind of methane fermentation material. In the batch fermentation a gram of dried water hyacinth can produce 0.344L methne. At room temperature, by mixing the pre-fermented water hyacinth with effluent in a ratio of 1:3 (calculated in COD), a gram of COD of the mixture can produce 0.556L methane with a continuous fermentation. The volume output of methane is 1.78L/(1,d). From our studies, an effective method of treating water hyacinth planted in anaerobic pond, which makes the effluent treatment system can be a biological cycle, is supplied.
Keywords: Anaerobic treatment; Effluent from SCR processing; Water hyacinth